2015
DOI: 10.1021/acs.molpharmaceut.5b00250
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Kinetic Insight into Spontaneous Cocrystallization of Isoniazid and Benzoic Acid

Abstract: Solid-state cocrystallization is of contemporary interest because it offers an easy and efficient way to produce cocrystals, which are recognized as prospective pharmaceutical materials. Research explaining solid-state cocrystallization mechanisms is important but still too scarce to give a broad understanding of factors governing and limiting these reactions. Here we report an investigation of the mechanism and kinetics of isoniazid cocrystallization with benzoic acid. This reaction is spontaneous; however, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 67 publications
2
40
0
Order By: Relevance
“…24 Spontaneous cocrystallization of INZ with benzoic acid helped in understanding the underlying mechanisms and contribution of external kinetic parameters. 25 Further, resveratrol was used to prepare a cocrystal with INZ for topical treatment of cutaneous tuberculosis. 26 Interestingly, it gave conglomerates with racemic tartaric acid in the presence of nonpolar liquid, whereas the polar liquid yielded a racemic salt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 Spontaneous cocrystallization of INZ with benzoic acid helped in understanding the underlying mechanisms and contribution of external kinetic parameters. 25 Further, resveratrol was used to prepare a cocrystal with INZ for topical treatment of cutaneous tuberculosis. 26 Interestingly, it gave conglomerates with racemic tartaric acid in the presence of nonpolar liquid, whereas the polar liquid yielded a racemic salt.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 64 demonstrated that the phase transformation of theophylline‒nicotinamide physical mixture to cocrystal was conducted without the assistance of any mechanical grinding. Another sample of spontaneous crystallization is the cocrystallization of isoniazid and benzoic acid, which illustrated that the rearrangement of cocrystals on the isoniazid surface was accelerated in the presence of moisture by promoting the interaction of isoniazid with benzoic acid vapor 65 . Additionally, premilling of cocrystal physical mixture reduced the induction time of cocrystal nucleation and increased the cocrystal formation rate.…”
Section: Cocrystal Preparationmentioning
confidence: 99%
“…Recently, it has been reported that cocrystals could be formed by exposing cocrystal components to suitable vapors 65 , 68 , 69 . Optical microscopy studies on moisture-induced carbamazepine‒nicotinamide cocrystal formation revealed that the deliquescence of components governed the cocrystal transformation, which led to localized dissolution of solid materials for crystallization 70 .…”
Section: Cocrystal Preparationmentioning
confidence: 99%
“…A method to reduce the amount of the solvent required for the CC screening is the use of solvent vapors instead of a liquid solvent. The CC formation from a physical mixture of the pure components due to water vapor sorption has been reported in the literature. Jayasankar et al showed that the underlying mechanism by which moisture sorption leads to CC formation is based on the hygroscopicity of CC components and the ability of a component to deliquesce (form a saturated liquid phase from the sorbed moisture). Dissolution of both CC components in the deliquesced small liquid phase generates CC supersaturation, nucleation, and growth .…”
Section: Introductionmentioning
confidence: 99%